Ethnic conflict and reconciliation in Sri Lanka - Manogaran, Chelvadurai (Honolulu : University of Hawaii Press, 1987)
Concerns the treatment of the Tamil minority in Sri Lanka.
Includes index.
Keywords: Tamil (Indic people) -- Sri Lanka -- Politics and government; Sri Lanka -- Politics and government; Sri Lanka -- Ethnic relations